Formulasi Sediaan Massage Oil dari Lavender, Citronella dan Chamomile dengan Olive Oil Sebagai Medium Pembawa - Nur Ermawati; Nazila Azka Zulvika (Asosiasi Riset Ilmu Kesehatan Indonesia, 2026)
This study aimed to form late and evaluate a natural massage oil preparation using a combination of lavender, citronella, and chamomile essential oils with olive oil as the carrier oil. The background of this research was based on the increasing public demand for natural body care products that are safe, non-irritating to the skin, and provide relaxation effects. The three essential oils used possess therapeutic activities, including relaxation, antimicrobial, anti-inflammatory effects, as well as the ability to relieve stress and muscle tension. The study employed three formulation variations (F1, F2, and F3) with different compositions of essential oils. The evaluation of the preparations included organoleptic tests, pH measurement, viscosity, specific gravity, physical stability testing, hedonic testing, and irritation testing. The organoleptic test results showed that all formulations had a liquid form, a deep light-yellow color, and a characteristic aroma corresponding to the dominant essential oil in each formulation. The pH values of all formulations were stable at 5, indicating safety for skin application. Viscosity values were within the ideal range for massage oil, between 4.124–4.735 cPs, and specific gravity values were within the standard range. Stability testing over 28 days revealed no significant changes in color, aroma, pH, or viscosity. The irritation test indicated that none of the formulations caused skin irritation in panelists. Hedonic testing showed that formulation 2 was the most preferred in terms of aroma, while formulation 3 was preferred for texture. Overall, all three formulations were considered stable, safe, and well accepted by consumers, indicating their potential use as natural massage oil products.